Children in the Crossfire: A Relational-Narrative Approach to Bridging Home and School - Barati, Tahereh (Murmurations: Journal of Transformative Systemic Practice, 2019)
In this article, I show how systemic social constructionist premises and practices transform, enliven, and expand the range of possibility within my everyday work. The article highlights intentional steps taken towards social collaboration in educational systems. Social collaboration is possible when "self" is regarded as relational and narrative. Individualistic definition of self is critically viewed as an obstacle to social collaboration. I present my work as a family therapist in the form of a case vignette that shows how collaborative work between parties in conflict can significantly impact outcomes for the child and others in relations to "bullying" at school. I describe how I work with students, parents, and school staff to utilise conflict in a way that improves conditions for children and brings about change in school systems. From this, new possibilities become available to co-construct meaningful and dialogical conversations between parents and school administrators. My argument is that this form of collaboration with families and their children supports change at multi layers.